REFLECTIONS ON TRAINING AND REQUIRED KNOWLEDGE FOR TEACH-ING PROFESSORS WHO WORK AT SECONDARY LEVEL FOR ADULTS - María Eugenia Cabrera; Noelia Bargas; Mariel Onnainty (Universidad Nacional del Nordeste, 2022)
In this article, we present the results of a research on the situation of the training of teachers who work at the secondary level for young and adult students in Buenos Aires Province. The objective was to survey public policies for the training of teachers in the modality and identify the representations of headmasters and professors on the training received and the necessary knowledge to undertake the teaching task, in the context of the secondary level being compulsory. A qualitative logic methodology was implemented. The empirical material derived from in-depth interviews led to the understanding of subject perspectives and the emergence of new issues. The teachers work at Educational Centers of Secundary Level (CENS), Fines and Popular High Schools in two districts of Buenos Aires Province. They receive heterogeneous groups and with complex educational backgrounds, in unequal institutional conditions. They teach at schools and venues, with specific school formats, which foresee curricular adaptations, tutorials, and pedagogical partner work. Some teachers identify the need for specific training, and they all face different problems related to teaching planning, curriculum selection, assessment, group work, while at the same time, they acquire knowledge with scarce collective spaces for critical review and systematization of what has been accomplished.